Two new chiggers of the genus Xinjiangsha (Acari: Trombiculidae) and a key to species of the genus - Kalúz, Stanislav; Kováčik, Ján (Zootaxa, 2012)
Two new chigger mites Xinjiangsha rychliki sp. nov. and Xinjiangsha stekolnikovi sp. nov. (Acari: Trombiculidae) aredescribed on the basis of single specimens. The larva of Xinjiangsha rychliki sp. nov. was captured by pitfall trap in Turkey(host unknown) and Xinjiangsha stekolnikovi sp. nov. was collected from the ears of Chionomys gud (Satunin) in Caucasus. The key to the known Xinjiangsha species is also presented.